Analysis of viscoelastic sandwich laminates using a unified formulation and a differential quadrature hierarchical finite element method. (1st February 2017) - Liu, Bo; Zhao, Liang; Ferreira, A.J.M.; Xing, Y.F.; Neves, A.M.A.; Wang, Jiayi
Abstract: In this paper we present a layerwise differential quadrature hierarchical finite element (DQHFE) model for the analysis of sandwich laminated plates with a viscoelastic core and laminated anisotropic face layers. The stiffness and mass matrices of elements are obtained by Carrera's Unified Formulation (CUF). The dynamic problem is solved in the frequency domain with viscoelastic frequency-dependent material properties for the core. The dynamic behavior of the model is compared with solutions found in literature. The DQHFE model was shown to be able to present highly accurate results using much less degrees of freedom than low order schemes like the finite element method.